239 Surgical Techniques Relating to First Carpometacarpal Joint Osteoarthritis - a Hand Therapy Perspective. (28th February 2022) - Menon, D.; Stavropoulos, S.
Abstract: Introduction: First carpometacarpal joint (CMCJ) osteoarthritis contributes a significant burden of disease. Patients with unremitting disease, despite conservative measures, may be considered for surgical intervention. Evidence has not identified superior outcomes relating to any one particular surgical technique. This study aims to identify whether a predisposition and preference towards an intervention exists in UK practice from the hand physiotherapist perspective. Method: An online questionnaire was distributed to UK-based hand therapists by electronic mail. Seven commonly utilised techniques in the management of first CMCJ osteoarthritis were listed as treatment options. Questions included demographic information, procedural experience, and ranking of these treatment options based on perceived post-operative functional outcomes. Results: 32 responses were recorded. All listed techniques were performed in UK practice. Trapeziectomy alone was the most widely used option, with 94% (n = 31) of respondents stating this intervention was performed in their centre of practice. Trapeziectomy with ligament reconstruction and interposition (LRTI) was associated with the highest rating relating to post-operative functional outcome as perceived by hand therapists. Partial arthroscopic trapezium resection with spacer was not favoured, with the lowest rating reported. Conclusions: This study has identified that trapeziectomy alone remains a widely used operative technique in first CMCJ osteoarthritis in UK practice with good post-operative outcomes relative to other options as perceived by hand therapists. The most favourable intervention was trapeziectomy with LRTI. However, no significant relationship was identified between the pre-defined interventional options and rating, which may suggest no superiority in any one particular technique.